Dual element MIMO planar inverted-F antenna for 5G millimeter wave application - H. M. R. Nurul; Z. Mansor; M. K. A. Rahim (Universitas Ahmad Dahlan, 2019)
This work presents a 28 GHz Dual Element Multiple Input Multiple Output (MIMO) Planar Inverted-F Antenna for millimeter wave 5G mobile terminal. The antenna design employs PIFA design concept as it is a common antenna type use for mobile phone as it provides wide bandwidth and good performance. The antenna design begins with a characterization of the single element PIFA design and then extended to Dual Element MIMO PIFA design. The single element PIFA design is enhanced to MIMO design by extending the ground plane and locate the second PIFA at the other end. Isolation between the antenna elements of the MIMO PIFA is analyzed by varying the gap distance between the antenna elements. The result for Envelope Correlation Coefficient, Diversity Gain and Multiplexing Efficiency is also presented. The simulation computed using Computer Simulation Technology (CST) Microwave Studio software.